IDENTIFICATION OF EPILEPTOGENIC ABNORMALITIES USING A HIGH-FIELD MR-SCANNER - V. A. Perepelov; M. S. Merkulova; E. M. Perepelova (Эпилепсия и пароксизмальные состояния, 2017)
Objective: to estimate the role of MR – tomography in epilepsy diagnostics. We have analyzed the main protocol used for examination of patients with epileptic seizures in anamnesis, as well as a number of modern techniques,  which help to get additional information about both structural and functional changes in the brain. We have described several types of pathological changes detected by us during examination of the patients from this group.